Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/acsomega.9b02238
|View full text |Cite
|
Sign up to set email alerts
|

Role of Wybutosine and Mg2+ Ions in Modulating the Structure and Function of tRNAPhe: A Molecular Dynamics Study

Abstract: Transfer RNA remains to be a mysterious molecule of the cell repertoire. With its modified bases and selectivity of codon recognition, it remains to be flexible inside the ribosomal machinery for smooth and hassle-free protein biosynthesis. Structural changes occurring in tRNA due to the presence or absence of wybutosine, with and without Mg2+ ions, have remained a point of interest for structural biologists. Very few studies have come to a conclusion correlating the changes either with the structure and flexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
(97 reference statements)
0
9
0
Order By: Relevance
“…Tetraloop simulations have been performed to identify native states and the underlying folding mechanisms. ,− MD simulations have been used to study various non-coding RNA functions, including binding to target sites as well as interactions with protein complexes . Larger RNA systems have also been simulated, such as tRNA and ribosomes; the effects of ions on tRNA behavior were explored in 2019, and AspRS-tRNA complexes were simulated in 2020 . However, both studies used understandably short (50–100 ns) simulations as significant computational power is required to simulate systems of this size.…”
Section: Introductionmentioning
confidence: 99%
“…Tetraloop simulations have been performed to identify native states and the underlying folding mechanisms. ,− MD simulations have been used to study various non-coding RNA functions, including binding to target sites as well as interactions with protein complexes . Larger RNA systems have also been simulated, such as tRNA and ribosomes; the effects of ions on tRNA behavior were explored in 2019, and AspRS-tRNA complexes were simulated in 2020 . However, both studies used understandably short (50–100 ns) simulations as significant computational power is required to simulate systems of this size.…”
Section: Introductionmentioning
confidence: 99%
“…Later, the importance of Mg 2+ binding for the tRNA tertiary structure has been debated over the years, questioning the prevalent action of nonspecific diffuse binding of Mg 2+ (or other divalent cations) or a specific Mg 2+ interaction [ 2 , 70 , 71 ]. A very recent paper demonstrated that magnesium ions are required by tRNAPhe for proper recognition of UUC/UUU codons during ribosomal interactions with tRNA [ 72 ].…”
Section: Biochemistry Of Magnesium To Understand the Consequences Of Its Deficienciesmentioning
confidence: 99%
“…Little is known about the structural properties of the tricyclic ring or the accompanying large side chains of these modifications that assist in maintaining the reading frame during translation [ 55 ]. Some molecular modeling studies suggest that restricted conformation sampling induced by the modification and its bulky side chains could be responsible for stabilizing codon–anticodon interactions and indirectly affecting translation [ 56 , 57 ].…”
Section: Classification Of Modified Rna Nucleosides Based On Their St...mentioning
confidence: 99%
“…The fully modified X-ray crystal structure of tRNA Phe [ 37 ] and the readily available AMBER parameters for its modified nucleotides from the database maintained by the Bryce Lab [ 68 ] have served as a robust system and act as a foundation for studying how modifications affect overall RNA dynamics. Specifically, studies on tRNA dynamics ([ 87 ] and how individual modifications alter the conformational landscape of the nucleotides to induce localized structural changes [ 57 , 69 , 88 ]) have benefited from this model system.…”
Section: Molecular Dynamics Simulations (Mds) Of Modified Rnamentioning
confidence: 99%